2010
DOI: 10.1088/0022-3727/43/15/155501
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and height detection of particle labels in an optical evanescent wave biosensor with single-label resolution

Abstract: Van Ijzendoorn, et al.. Mobility and height detection of particle labels in an optical evanescent wave biosensor with singlelabel resolution. Journal of Physics D: Applied Physics, IOP Publishing, 2010, 43 (15) AbstractParticle labels are used in biosensors to detect the presence and concentration of analyte molecules. In this paper we demonstrate an optical technique to measure the mobility and height of bound particle labels on a biosensor surface with single-label resolution. The technique is based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…[16] The DNA strands are tagged with Texas Red on one end and biotin on the other end; [16] the particles have a streptavidin coating and the cartridge surface is coated with polyclonal antibodies against Texas red. [11] After coating the cartridge, the surface is blocked in a PBS buffer containing 1% (w/v) BSA, 10% (w/v) sucrose and 0.1% (w/v) sodium azide and stored at 4°C. Before use, the cartridge is washed with 100 mM borate buffer (pH 8.5) containing 0.05% (v/v) Tween 20.…”
Section: Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…[16] The DNA strands are tagged with Texas Red on one end and biotin on the other end; [16] the particles have a streptavidin coating and the cartridge surface is coated with polyclonal antibodies against Texas red. [11] After coating the cartridge, the surface is blocked in a PBS buffer containing 1% (w/v) BSA, 10% (w/v) sucrose and 0.1% (w/v) sodium azide and stored at 4°C. Before use, the cartridge is washed with 100 mM borate buffer (pH 8.5) containing 0.05% (v/v) Tween 20.…”
Section: Assaymentioning
confidence: 99%
“…non-spherical, rough surface and inhomogeneous content) can show an increase in scattering intensity fluctuations, thus leading to an overestimation of the height displacement. [11] MagSense particles are observed in Transmission Electron Microscopy images to be smooth and spherical, but some particles may still have minor defects or an inhomogeneous content, leading to a small increase in measured height, which becomes noticeable for short tether lengths. We examined the occurrence of heights smaller than the tether length for both particle types by studying the intensity-position plots, and found many differences in mobility between different cases.…”
Section: Mobility Differences Between Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that measuring the thermally induced intensity fluctuations of single, optically uniform particles leads to accurate measurements of the height distribution of the particles. 22 The histogram of the measured scattered intensity ͑30 s measurement at 60 Hz, exposure time of 1 ms͒ of the images of a single MagSense particle bound to 290 bp DNA is shown in Fig. 3͑a͒.…”
Section: Fig 2 ͑A͒mentioning
confidence: 99%
“…We repeated this measurement for four particles, each bound to DNA of a different length. For each particle, we calculated the maximum height displacement ⌬h = d p ln͑I max / I min ͒, where d p is the penetration depth of the evanescent field ͑95 nm in our setup 22 ͒, and I max and I min are the maximum and minimum intensity values for which the measured probability decreases below 8%, equivalent to a thermal energy larger than 2.5 k B T. In Fig. 3͑b͒ the maximum height displacement of the four particles is plotted as a function of the buffer molarity.…”
Section: Fig 2 ͑A͒mentioning
confidence: 99%